Managing conflict and trust as coopetition within alliance partnerships in an emerging economy - Hao Shen; Yu Gao; Chenlu Zhang (South African Journal of Business Management, 2019)
Background: Trust and conflict represent the critical foundation characterising the inter-firm relationship of cooperation and competition, and their co-existence as coopetition within an alliance partnership. The literature has often regarded conflict and trust as uni-dimensional variables to clarify their interactive influences. However, few studies has explicitly investigate how these two opposite forces and their sub-dimensions may interact and create synergic effects in alliance partnerships in emerging economies.Objectives: This study applies a coopetition perspective to articulate the complex interactive nature of conflict and trust between partners, aiming at revealing how specific patterns of conflict (task and emotional) and trust (cognitive and affective) interact with each other in impacting the focal firm's performance within the alliance partnership.Method: Using survey data collected from 490 sampled firms in China, we ran three regression models to test four hypotheses from the interactive matrix between different dimensions of conflict and trust.Results: The results indicate that the coupled pattern (the interaction between emotional conflict and affective trust) and the compatible pattern (the interaction between task conflict and cognitive trust) could improve firm performance, whereas the dysfunctional pattern (the interaction between emotional conflict and cognitive trust) and the mismatched pattern (the interaction between task conflict and affective trust) could harm firm performance within alliance partnerships.Conclusion: The new findings imply diverse ways to combine conflict and trust to achieve the best synergistic effect for allied firms in emerging economies, and thus extend and enrich the literature by providing contextual knowledge regarding `conflict and trust as coopetition phenomena' in relevant fields.
Keywords: 650